Drug utilization pattern of antihypertensive agents in patients of hypertensive nephropathy in a tertiary care hospital: a cross sectional study - Shah, Jay; Balraj, Avinash (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Objective of the study was to determine the drug utilization pattern of antihypertensive agents in patients of hypertensive nephropathy in a tertiary care teaching hospital. Methods: This was a prospective observational study carried out in Index medical college and Hospital, Indore over a period of three 4 months. A total of 60 patients aged 40-79 years taking treatment for hypertension with associated nephropathy were enrolled in the study. All the relevant data were collected and drug utilization pattern of antihypertensive agents was determined. The study evaluated the percentage of use of multidrug therapy, drugs prescribed from Essential Drug List (EDL) and prescriptions with generic name. The cost of antihypertensive drugs used per day was calculated and linked with socioeconomic status of the patients. Results: Evaluation of the prescriptions demonstrates that a total of 63.3% males and 36.7% females with mean age of 58.9±11.9 years were enrolled out of which 70% patients were on multidrug therapy while only 30% were on monotherapy. Though only 16.67% patients were prescribed generic drugs but it did not affect the economic condition of the patient as most of enrolled patients belong to upper middle class. Conclusions: The prescriptions analysed were in accordance to guidelines of JNC-8 (Joint National Committee - 8) and most of the prescriptions were found to be rational and it also shows that management of hypertensive nephropathy needs combination therapy.